2014
DOI: 10.1128/aac.01726-13
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus UL97 Kinase Is Involved in the Mechanism of Action of Methylenecyclopropane Analogs with 6-Ether and -Thioether Substitutions

Abstract: cMethylenecyclopropane nucleoside (MCPN) analogs are being investigated for treatment of human cytomegalovirus (HCMV) infection because of favorable preclinical data and limited ganciclovir cross-resistance. Monohydroxymethyl MCPNs bearing ether and thioether functionalities at the purine 6 position have antiviral activity against herpes simplex virus (HSV) and varicella-zoster virus (VZV) in addition to HCMV. The role of the HCMV UL97 kinase in the mechanism of action of these derivatives was examined. When t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Mutations that knock out UL97 kinase activity, e.g. by altering a critical residue such as K355, are inherently highly resistant to maribavir and cross-resistant to ganciclovir, but have no demonstrated clinical relevance because of the resulting severe viral growth impairment [12,15]. This includes some of the mutants in Table 1 that show high-level maribavir resistance (>200-fold increased EC50).…”
Section: Genetic Mechanisms Of CMV Drug Resistancementioning
confidence: 99%
“…Mutations that knock out UL97 kinase activity, e.g. by altering a critical residue such as K355, are inherently highly resistant to maribavir and cross-resistant to ganciclovir, but have no demonstrated clinical relevance because of the resulting severe viral growth impairment [12,15]. This includes some of the mutants in Table 1 that show high-level maribavir resistance (>200-fold increased EC50).…”
Section: Genetic Mechanisms Of CMV Drug Resistancementioning
confidence: 99%
“…MBX 2168 is phosphorylated by UL97, a serine-threonine protein kinase encoded by HCMV and resistance to MBX 2168 maps to this viral kinase (Komazin-Meredith et al, 2014). MBX 2168 is also a substrate of the HHV-6 U69 protein kinase, which is a homologue of UL97 (Komazin-Meredith et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The proposed mechanism of action of these compounds involves their sequential phosphorylation to a triphosphate, which then inhibits viral DNA polymerase. We previously showed that the HCMV protein kinase UL97 and the HHV-6 protein kinase U69 are involved in phosphorylation of MCPNs to their monophosphates (Komazin-Meredith et al, 2013; Komazin-Meredith et al, 2014). The antiviral activity of these compounds was, however, less dependent on the activity of the HCMV UL97 kinase than was CPV, suggesting the involvement of a host enzyme in their phosphorylation (Komazin-Meredith et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, 6-alkoxy and 6-alkylthio derivatives of synguanol have been synthesized that showed improved in vitro antiviral activities against CMV and other herpesviruses (8). As with ganciclovir, the CMV UL97 kinase is involved in the initial phosphorylation of these compounds, and drug-resistant UL97 mutants have been described (9). The aim of the present study was to compare the activities of synguanol, a 6-ether derivative (MBX2168), a 6-thioether derivative (MBX1616), and cyclopropavir ( Fig.…”
mentioning
confidence: 99%